(untitled) (Journal of Hama University, 2026)
Obstacles to the Application of Developed Science Curricula in the Basic Education Stage from the point of View of Teachers Abstract; The current research aims to identify the Obstacles to the Application of Developed Science Curricula in the Basic Education Stage from the point of View of Teachers. The researcher used the descriptive analytical method. The research sample consisted of (204) male and female science teachers in the primary education stage. The research tool was a questionnaire consisting of five domains: (Obstacles related to basic requirements، obstacles related to the nature of the curriculum، obstacles related to training programs، obstacles related to the teacher، obstacles related to the student). The research results showed that the academic requirements domain came in first place with a relative metering weight of (83.4)، followed in second place by the domain related to the teacher with a relative metering weight of (77.75). The domain related to the nature of the curriculum came in third place with a relative metering weight of (75.44)، Followed by the domain related to the student in fourth place with a relative metering weight of (75.05). While the domain related to training courses came in last place with a relative metering weight of (74.17). However، the results also showed that there are differences between the average scores of teachers according to the experience variable، which are attributed to teachers with experience more than 10 years. Also، there are differences between teachers’ grades according to the educational qualification variable in favour of teachers who hold an institute certificate degree. Add to that. There are also differences between teachers’ grades according to the variable of enrolling in training courses، in favour of teachers who did not enroll in training courses. According to the results، the research presented a set of proposals: Conducting training courses for teachers to keep up with developments in curricula and learn about the modern teaching methods that appropriate for it ، providing the necessary equipment and materials to enable the teacher from implementing the curriculum in an appropriate manner and providing classroom teachers with the opportunity to complete postgraduate studies and participate in curriculum development. Keywords: Obstacles، developed curricula، primary school teachers